CHECKING OF TECHNICAL BRIDGES’ STATE BY PASSIVE VIBRATIONAL DYNAMICS METHODS - Redchenko, V. P. (Science and Transport Progress, 2010)
In the article the results of studies of the passive vibration test methods and the possibilities of using them for determining and monitoring of technical condition of bridges are presented.